INVENTARISASI FASILITAS WISATA DALAM MENDUKUNG PENGEMBANGAN DESTINASI WISATA SUNGAI JANIAH KANAGARIAN TABEK PANJANG DI KECAMATAN BASOKABUPATEN AGAM - Hendri Azwar; Himawan Brahmantyo (Ensiklopedia of Journal, 2019)
This study aims to identify and analyze tourist facilities at the Sungai Janiah Tourism Destination, Baso Sub-district, Agam Regency. This research uses a qualitative approach with a SWOT analysis. Data collection techniques through interviews, observation, and documentation. Data were analyzed qualitatively, including reduction, presentation, and conclusion drawing. The results showed that the potential for developing tourist facilities in this tourist destination is the utilization of community houses and traditional houses as homestays. Developing restaurants by utilizing community land and existing buildings with investors' help, creating regional souvenirs, renovating souvenir sales places, improving public facilities such as toilets, seating, parking lots, and public areas, and improving their cleanliness. Finally, the collaboration of all elements in fostering managers and the community to realize comfortable tourist facilities for tourists.Keywords: Tourism Facilities; Tourism Destinations.